EVALUATION OF OCCUPATIONAL SAFETY AND HEALTH MANAGEMENT SYSTEM POLICIES AT THE SUKABUMI CITY ENVIRONMENTAL AGENCY - Huda, Fadlul; Fajar F.Y Basori, Yana; Purwanti, Dian (Penerbit Lafadz Jaya, 2025)
This study aims to evaluate the SMK3 policy at the Sukabumi City Environmental Agency with a focus on effectiveness, efficiency, adequacy, equity, responsiveness, and accuracy of implementation. This study uses a qualitative approach with a case study method and data analysis of the Miles and Huberman interactive model. Data were collected through observation, interviews, documentation, and triangulation. The research informants include the head of the agency, the head of the field, the waste collection officer, and the manager of the landfill (TPA). The results of the study explained that the effectiveness of the implementation of SMK3 has not been optimal, as seen from the lack of PPE use and lack of training. The efficiency of resource use has not been maximized, with limited budgets and lack of coordination. The adequacy of tools and training is not enough to protect workers. The equitable distribution of PPE has been carried out but the quality still needs to be improved. The responsiveness where the SMK3 policy has not fully responded to the needs of officers. And the accuracy in the implementation of SMK3 in the field is not fully in accordance with existing guidelines. The research contribution is to enrich the literature on the implementation of the Occupational Safety and Health Management System (SMK3) in the government sector, especially the Environment Agency, by identifying factors that affect policy effectiveness, such as management commitment, resource availability, and employee participation. This study provides strategic recommendations to improve the effectiveness of SMK3 policies, including the provision of adequate PPE, the preparation of SOPs, routine training, increased coordination between agencies, and community education. This research can be used as a basis in decision-making for the improvement of SMK3 policies at the local level, by emphasizing the importance of monitoring, periodic evaluation, and adequate resource allocation to ensure the occupational safety and health of waste collection officers.